Impact of Prosopis velutina Wooton on the Composition and Diversity of Native Woody Species in a Semi-Arid Zone along the Molopo River, South Africa - Makuété A. P. Tiawoun; Pieter W. Malan; Alvino A. Comole; Moleseng C. Moshobane (Plants, 2023)
Invasive alien species represent one of the main threats to biodiversity and species extinction. This is the case for the genus Prosopis, among which Prosopis velutina is the most invasive and common tree species along the Molopo River in the North-West Province, impacting native plant communities. However, its impact on the composition and diversity of native woody species remains poorly investigated in the area. Thus, this study aimed to assess the impact of P. velutina on native woody plant composition and diversity across three sites along the Molopo River. At each site, five quadrats of 20 × 20 m2 were randomly established in invaded and adjacent uninvaded stands. A comparative methodological approach was adopted, and the woody plants in invaded and uninvaded stands with similar site conditions were sampled. The results showed that native woody species density differed significantly (p < 0.05) between invaded and uninvaded stands, except for Bray sites, where there was a marginal difference (p = 0.6). The overall native woody species density decreased by 79.7% in the invaded stand. However, non-metric multidimensional scaling (nMDS) and analysis of similarity (ANOSIM) indicated significant differences in native tree composition between invaded and uninvaded stands at all sites. In all three sites, all ecological indices had significantly lower values in invaded stands compared to uninvaded stands. The decrease in all ecological indices in invaded over uninvaded stands indicated that P. velutina invasion reduced the diversity of native woody plant species. Due to the incessant spread of P. velutina, it may become a long-term dominant species with an increasing impact on the native vegetation. Therefore, the findings of this study call for urgent management and appropriate control measures against the ongoing spread of this invader within the riparian zones of the Molopo River in North-West Province.